Analisis Minyak Jelantah Sebagai Bahan Bakar Biodiesel dengan Proses Transesterifikasi - Hadrah Hadrah; Monik Kasman; Fitria Mayang Sari (Universitas Batanghari Jambi, 2018)
Waste cooking oil is used oil that has been used for domestic purposes and has undergone changes, both physically and chemically. One effort that can be done to reduce the adverse effects of used cooking oil is changed the material used cooking oil into biodiesel. In this study of biodiesel production from waste cooking oil is done by using biodiesel transesterification reaction as generally through a pretreatment in order to reduce the number of Free Fatty Acid in cooking oil. The high number of Free Fatty Acid will complicate the separation of glycerol from biodiesel so that production of biodiesel will be slight. Test parameters of biodiesel quality produced by transesterification process refers to the Indonesian biodiesel quality standard ISO 7182: 2015. The production of biodiesel from used cooking oil in this experiment using variations methanol and sodium hydroxide solution ratio to the used cooking oil is 1: 2; 1: 4 and 1: 8. Test results showed that the quality of biodiesel is in compliance with ISO 7182: 2015 on the parameters of viscosity, density and flame test. While the Free Fatty Acids remained above the quality standard ISO 7182: 2015.Keywords : Waste cooking oil, Transesterification, Biodiesel